Combined effects of fungal β-glucan and Zataria multiflora essential oil on phagocytosis in Balb/C mice - Hojjatollah Shokri; Alireza Khosravi (Shahrekord University of Medical Sciences, 2016)
Introduction: Natural substances have been used since ancient times for treatment of a range of diseases and have represented stimulatory effects on the function of innate immunity. The purposes of this study were to prepare β-glucan from S. cerevisiae and to assess the efficacy of purified β-glucan, Zataria multiflora (Z. multiflora) essential oil and their complex on phagocytosis in Balb/c mice. Methods: β-glucan was purified during three stages including alkaline-acid treatment (S1), DEAE sephacel chromatography (S2) and con-A sepharose chromatography (S3). Z. multiflora essential oil was extracted by water-distillation using Clevenger-type apparatus. The chemical composition of Z. multiflora essential oil was analyzed by a GC/MS system. β-glucan (15 mg/kg), Z. multiflora essential oil (100 mg/kg) and their complex (the same doses) were injected into Balb/c mice intraperitoneally (IP). The blood samples were collected at days 4 and 7 after injection and phagocytic activity was assayed by chemiluminescence method. Results: The results showed that the ratios of mannan to β-glucan were 70.3 to 29.7 for S1, 71.9 to 28.1 for S2 and zero to 100 for S3 (purified β-glucan). The major components of Z. multiflora were carvacrol (61%) and thymol (25%). Phagocytosis index means exhibited significant increases at day 4 (246%, 165% and 367%) and day 7 (242%, 235% and 309%) in mice treated with purified β-glucan, Z. multiflora essence, and their complex when compared to control mice, respectively (P < 0.05). Conclusion: The results suggest that the complex of β-glucan and Z. multiflora oil might be used to immunize individuals as prophylactic and/or therapeutic adjuvant in immunocompromised subjects.